2019
DOI: 10.1186/s12891-019-2429-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of patellofemoral arthrokinematic motion quality in open and closed kinetic chains using vibroarthrography

Abstract: BackgroundKnee movements performed in open (OKC) and closed (CKC) kinetic chains generate various patterns of muscle activities and especially distinct contact stresses in the patellofemoral joint (PFJ). In contrast to these features, the arthrokinematic motion quality (AMQ) of the PFJ has not been compared between mentioned conditions. In this study we performed vibroarthrographic analysis of AMQ in movements performed in OKC and CKC, in healthy subjects and individuals with chondromalacia patellae, to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 36 publications
3
48
0
Order By: Relevance
“…Kiselev et al [2] showed a diagnostic accuracy of the acoustic emissions measurement from good to very good. Moreover, knee sounds produced by the articulation of joint components not only contain information on the joint health and morphology, but also have been well discussed as surrogates of knee joint loading during motion [1,4,[6][7][8]. These findings appear to be particularly important, because vibroarthrography presents a new perspective on knee arthrokinematics.…”
Section: Introductionmentioning
confidence: 99%
“…Kiselev et al [2] showed a diagnostic accuracy of the acoustic emissions measurement from good to very good. Moreover, knee sounds produced by the articulation of joint components not only contain information on the joint health and morphology, but also have been well discussed as surrogates of knee joint loading during motion [1,4,[6][7][8]. These findings appear to be particularly important, because vibroarthrography presents a new perspective on knee arthrokinematics.…”
Section: Introductionmentioning
confidence: 99%
“…Following previous publications, our experiment assumed that the intensity of acquired vibroacoustic emission waves is closely associated with the kinetic friction and represents friction-induced vibrations generated by relative sliding and rolling of adjacent articular surfaces. From biomechanical and tribological points of view the ability of the articular surfaces to move smoothly against each other with low frictional noise indicates optimal arthrokinematic motion related with low kinetic friction, and as a result contributes to slow wear of cartilage [20]. The presented ndings of this study con rm that during a knee exion-extension movement with the load of the body weight, the PFJ arthrokinematic motion possesses low-vibration characteristics, despite relatively high values of articular surface load, typical for this analyzed condition.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies, assessment of the PFJ arthrokinematic motion quality was performed with an accelerometer sensor placed 1 cm above the apex of the patella [11,20,36].…”
Section: Assessment Of Arthrokinematic Motion Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous studies, assessment of the PFJ arthrokinematic motion quality was performed with an accelerometer sensor placed 1 cm above the apex of the patella [11,20,37].…”
Section: Assessment Of Arthrokinematic Motion Qualitymentioning
confidence: 99%